Enhanced CO2 outgassing in the Southern Ocean from a positive phase of the Southern Annular Mode - Lovenduski, Nicole S.; Gruber, Nicolas; Doney, Scott C.; Lima, Ivan D. (Global Biogeochemical Cycles, 2007)
Author Posting. © American Geophysical Union, 2007. This article is posted here by permission of American Geophysical Union for personal use, not for redistribution. The definitive version was published in Global Biogeochemical Cycles 21 (2007): GB2026, doi:10.1029/2006GB002900. We investigate the interannual variability in the flux of CO2 between the atmosphere and the Southern Ocean on the basis of hindcast simulations with a coupled physical-biogeochemical-ecological model with particular emphasis on the role of the Southern Annular Mode (SAM). The simulations are run under either pre-industrial or historical CO2 concentrations, permitting us to separately investigate natural, anthropogenic, and contemporary CO2 flux variability. We find large interannual variability (±0.19 PgC yr−1) in the contemporary air-sea CO2 flux from the Southern Ocean (<35°S). Forty-three percent of the contemporary air-sea CO2 flux variance is coherent with SAM, mostly driven by variations in the flux of natural CO2, for which SAM explains 48%. Positive phases of the SAM are associated with anomalous outgassing of natural CO2 at a rate of 0.1 PgC yr−1 per standard deviation of the SAM. In contrast, we find an anomalous uptake of anthropogenic CO2 at a rate of 0.01 PgC yr−1 during positive phases of the SAM. This uptake of anthropogenic CO2 only slightly mitigates the outgassing of natural CO2, so that a positive SAM is associated with anomalous outgassing in contemporaneous times. The primary cause of the natural CO2 outgassing is anomalously high oceanic partial pressures of CO2 caused by elevated dissolved inorganic carbon (DIC) concentrations. These anomalies in DIC are primarily a result of the circulation changes associated with the southward shift and strengthening of the zonal winds during positive phases of the SAM. The secular, positive trend in the SAM has led to a reduction in the rate of increase of the uptake of CO2 by the Southern Ocean over the past 50 years. This work was supported by NASA headquarters under ...